2021
DOI: 10.1002/suco.202100274
|View full text |Cite
|
Sign up to set email alerts
|

Alkali activated cement mixture at ambient curing: Strength, workability, and setting time

Abstract: The success of ordinary Portland cement (OPC) comes at a risk to the environment because of the large carbon dioxide emissions associated with cement manufacturing. This has led the scientific community to look for alternative cementitious materials with lower environmental impact. Alkali activated cement (AAC) is an excellent alternative to this end. In this study, the effect of binder content, alkaline solid to binder ratio (AS/B), sodium silicate to sodium hydroxide solids ratio (SS/SH), and total water con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This is an important finding showing that a limit is required on the amount of alkaline content in the mixture for optimum mechanical and durability behaviors. Tekle et al 26 studied 0.14, 0.18, and 0.22 AS/B ratios. The maximum 28‐day compressive strength was obtained at 0.18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important finding showing that a limit is required on the amount of alkaline content in the mixture for optimum mechanical and durability behaviors. Tekle et al 26 studied 0.14, 0.18, and 0.22 AS/B ratios. The maximum 28‐day compressive strength was obtained at 0.18.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in AS/B (FGAAC-AS/B) decreased the compressive strength, while an increase in the SS/SH ratio (FGAAC-SS/SH) increased the strength. Further details regarding the effect of each of the parameters on the compressive strength can be found in Tekle et al 20,26…”
Section: Compressive Strengthmentioning
confidence: 99%
“…An exponential urbanization and infrastructure development have created a vital need for a sustainable construction material with lower carbon dioxide (CO 2 ) emission [ 1 , 2 ]. Researches confirmed that there is about one kilogram of carbon dioxide emission per one kilogram production of Ordinary Portland Cement (OPC) [ 3 , 4 , 5 , 6 ]. Thus, the construction industry is a major source of greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Due to the economic and environmental concerns mentioned above, production of sustainable alternative binders to PC has gained considerable attention. 4,30,31 Geopolymers, also called alkali activated binders, are new generation binder types that stand out among the searches for green alternatives binders. 7,9,32,33 Geopolymer binders are semi crystal inorganic polymers synthesized by geopolymerization reactions between highly alkaline solutions (sodium hydroxide and sodium silicate) and aluminosilicate precursors (natural or waste pozzolans).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the economic and environmental concerns mentioned above, production of sustainable alternative binders to PC has gained considerable attention 4,30,31 . Geopolymers, also called alkali activated binders, are new generation binder types that stand out among the searches for green alternatives binders 7,9,32,33 .…”
Section: Introductionmentioning
confidence: 99%